Advances in multimedia information processing - PCM 2013 : 14th Pacific-Rim Conference on Multimedia, Nanjing, China, December 13-16, 2013. Proceedings - Ngo, Chong-Wah; Tang, Jinhui; Zhou, Zhi-Hua; Hauptmann, Alexander G.; Yan, Shuicheng (Lecture Notes in Computer Science,, 2013)
This book constitutes the proceedings of the 14th Pacific-Rim Conference on Multimedia, PCM 2013, held in Nanjing, China, in December 2013. The 30 revised full papers and 27 poster papers presented were carefully reviewed and selected from 153 submissions. The papers cover a wide range of topics in the area of multimedia content analysis, multimedia signal processing and communications, and multimedia applications and services.